PENGEMBANGAN APLIKASI MOBILE SISTEM LAPORAN WARGA MENGGUNAKAN METODE MOBILE APPLICATION DEVELOPMENT LIFE CYCLE (MADLC) (STUDI KASUS : DESA GANGGANG PANJANG) - Nico Mayharis; Wildan Suharso; Briansyah Setio Wiyono (Jurnal Ilmiah Informatika, 2026)
The citizen reporting system in Ganggang Panjang Village is still conducted manually, requiring residents to visit the village office directly to report infrastructure issues, public facility problems, and emergency conditions. This condition causes delays in response, loss of documentation, and low transparency in complaint handling. This study aims to design, implement, and evaluate a mobile-based citizen reporting application using the Mobile Application Development Life Cycle (MADLC) methodology, which consists of seven phases: Identification, Design, Development, Prototyping, Testing, Deployment, and Maintenance. The application was developed using the Flutter framework and Supabase backend, featuring GPS-based reporting, real-time status tracking, an analytics dashboard, and two-way notifications. Functional testing using Black Box Testing on 18 test scenarios showed a 100% success rate. Usability testing using the System Usability Scale (SUS) with 15 respondents resulted in an average score of 82.08, categorized as Excellent. These results demonstrate that MADLC with iterative prototyping phases produces an application that is functional, user-friendly, and suitable for rural communities with varying levels of digital literacy.